HUBUNGAN KUALITAS TIDUR DENGAN TINGKAT KONSENTRASI MAHASISWA KEBIDANAN TINGKAT I DAN II UNIVERSITAS BATAM - Khairiyah, Siti; Anjan, Arum Dwi (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2017)
Sleep can improve someone ability and concentration. Bad sleep quality can impact in decreasing the cognitive function, slower the psychomotor and impair the concentration. This research aims to investigate the correlation of sleep quality and the concentration level of midwifery student year 1 & 2 in University of Batam . This research is quantitative employing cross-sectional approach conducted from April to May 2017. It is involving 26 of DIII Midwifery student of university of Batam year 1 & 2 as the respondents. The data collecting technique is Total sampling. The data analyzing technique is chi-square test. The result of the research reveals most of student posses good sleep quality is about 35 (56,5%), While most of student posses the good concentration is about 36 respondents (58.1%) with p value = 0.000 (<0.05). From the findings, it can be concluded that there is correlation between sleep quality and the concentration level of midwifery student 1 & 2 in University of Batam. In suggestion, student posses good sleep quality are expected to maintain what they have while the student posses bad sleep quality are also expected to improve to be better.